PE (polyethylene) material containing nano reinforcing material and preparation method of PE material

Through the combination of nano reinforcement materials and high-temperature additive components, the problem of insufficient high-temperature resistance in high-temperature environments is solved, and its mechanical properties and toughness are significantly improved, the service life is extended and the application field is broadened.

CN119264541AActive Publication Date: 2025-01-07HANGZHOU JINTAI PLASTIC IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411398892.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Polyethylene materials have poor high temperature resistance in high temperature environments, resulting in a decrease in mechanical properties, affecting structural stability and service life, and limiting their application in electrical cable sheaths and electronic equipment.

Method used

By preparing nanoreinforced materials and high-temperature additive components, combined with chemical modification and crosslinking technology, the mechanical properties and high-temperature resistance of polyethylene materials are improved. Nano C60 is chemically modified and combined with hyperbranched polyester to form an interpenetrating network to enhance the mechanical properties of polyethylene materials; polyisoprene produces thermally stable high-temperature additive components through epoxidation and ring-opening reaction. , improve the toughness and high temperature resistance of polyethylene.

Benefits of technology

It significantly improves the tensile strength, elongation of break and Vica softening temperature of polyethylene materials, enhances its stability and safety in high-temperature environments, extends service life, and broadens the application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264541A_ABST
    Figure CN119264541A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a PE material containing a nanometer reinforcing material and a preparation method of the PE material, the PE material comprises the following raw materials: low-density polyethylene, the nanometer reinforcing material, a high-temperature-resistant additive component, a compatilizer, a lubricant and an antioxidant; low-density polyethylene is used as a matrix, a nano reinforcing material is added, and nano C60 and hyperbranched polyester are grafted, so that the compatibility of nano C60 and the matrix is effectively improved, the agglomeration phenomenon of nano C60 in the matrix is avoided, the advantages of nano C60 are better played, and the mechanical property of the PE material is improved; a high-temperature-resistant additive component is added, a polyisoprene molecular chain with good flexibility is used for dispersing and absorbing external impact energy, the toughness of a matrix is improved, a diphenyl ether-based high-temperature-resistant rigid ring is introduced into a polyisoprene structure, and the diphenyl ether-based high-temperature-resistant rigid ring can act with a compatilizer in the processing process to be crosslinked with the matrix, so that the mechanical property of the matrix is improved, and the mechanical property of the matrix is improved. The high temperature resistance and the toughness of the PE material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a PE material containing a nano-reinforcement material and a preparation method thereof. Background Art

[0002] Polyethylene (PE), as a thermoplastic, is one of the most widely used and produced plastics in the current plastics industry, and plays an indispensable role in modern industry and life. Polyethylene has many advantages such as corrosion resistance, not easily corroded by most acid, alkali, and salt chemicals, non-conductive materials, good electrical insulation, easy processing and molding, and can be processed into products of various sizes and shapes through a variety of processes. It is resistant to low temperatures, non-toxic and tasteless, light in weight, and can be recycled and reused. Polyethylene is widely used and can be prepared into film products such as plastic wrap and ground film, prepared into daily necessities such as basins and buckets, prepared into pipes for water supply, agricultural irrigation, and gas transportation, etc., prepared into packaging materials, automotive interiors, automotive tires, product housings and components of electronic equipment, etc.

[0003] However, polyethylene is used in electrical cable sheath materials and electronic equipment, which not only requires excellent mechanical properties, but also protects the integrity of the internal structure from external environmental interference, and can prevent the material from being damaged when subjected to external force impact or stress concentration; in addition, when polyethylene materials are in a high temperature environment for a long time, due to the poor high temperature resistance of polyethylene materials, they are easy to soften and deform, which accelerates the aging process of the material, resulting in a decrease in mechanical properties such as tensile strength, affecting structural stability, resulting in a shortened service life of the material, and posing safety hazards. Therefore, polyethylene materials still have the defects of insufficient mechanical properties and poor high temperature resistance, which limits the application of polyethylene materials. Nano-reinforcement materials are composed of nano-sized particles or fibers, have a high specific surface area and unique physical and chemical properties, and are added to polymer materials to improve basic properties. The use of nano-reinforcement materials to modify polyethylene materials has important research value; the patent with publication number CN110229400B discloses a PE nano-composite material and a preparation method thereof, wherein a paste-like nano-material mixture is prepared, and then mixed and stirred with PE particles to form a blend, and the blend is melt-blended to obtain a PE nano-composite material, and the tensile strength and impact strength of the nano-composite material are improved on the basis of the PE base material. The invention prepares nano-reinforcement materials and high-temperature resistant additive components, and adds them into polyethylene materials to improve the mechanical properties and high-temperature resistance of the polyethylene materials, thereby making the polyethylene materials safer and more reliable and expanding the application range of the polyethylene materials. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a PE material containing nano-reinforcement material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A PE material containing nano-reinforcement material comprises the following raw materials in parts by weight: 65-85 parts of low-density polyethylene, 3-5 parts of nano-reinforcement material, 4-6 parts of high-temperature resistant additive components, 4-8 parts of compatibilizer, 0.5-2.5 parts of lubricant, and 0.5-2.5 parts of antioxidant.

[0007] Furthermore, the preparation method of the nano-reinforcement material comprises the following steps:

[0008] Step A, adding nano C60 to a toluene solution, stirring evenly, adding 3-chloropropylene and an initiator, introducing nitrogen protection, raising the temperature to 65-75°C, reacting for 6-8h, collecting the product, washing, and vacuum drying to obtain modified nano C60;

[0009] Step B, adding modified nano C60 into dimethyl sulfoxide, adding terminal hydroxyl hyperbranched polyester and alkaline catalyst, raising the temperature to 70-90° C., stirring and reacting for 5-8 hours, washing, vacuum drying, and obtaining nano reinforced material.

[0010] By adopting the above technical scheme, 3-chloropropylene is utilized to chemically modify nano C60 to obtain modified nano C60 with active chlorine substituents, and the active chlorine substituents in the modified nano C60 structure are utilized to react with the hydroxyl in the terminal hydroxyl hyperbranched polyester structure to obtain nano reinforcers. The surface of the nano C60 after chemical modification contains an organic transition layer, which can effectively improve the compatibility with the polyethylene matrix, so that the nano reinforcers have good dispersibility in the polyethylene matrix, prevent the nano reinforcers from agglomerating, improve the bonding force with the polyethylene matrix, and give full play to the advantages of nano C60, strengthen the mechanical properties of the polyethylene matrix, and in addition, the hyperbranched polyester has a unique mesh structure, contains a large amount of branching points, can extend to each region of the polyethylene matrix, produce physical crosslinking, form an interpenetrating network with the polyethylene molecular chain, strengthen the interface bonding force between the polyethylene matrix, make the polyethylene material molecular chain structure more compact, when subjected to external force, the interpenetrating network can more effectively disperse and transfer stress, and further improve the mechanical properties of the polyethylene material.

[0011] Furthermore, in step A, the initiator is azobisisobutyronitrile or azobisisoheptanenitrile.

[0012] Furthermore, in step B, the alkaline catalyst is potassium carbonate or sodium carbonate.

[0013] Furthermore, the preparation method of the high temperature resistant additive component comprises the following steps:

[0014] S1. Add polyisoprene to a toluene solution, mix well, add acetic acid and hydrogen peroxide, then raise the temperature to 45-55° C., react for 3-5 hours, precipitate, wash, and vacuum dry to constant weight to obtain epoxidized polyisoprene;

[0015] S2. Add epoxidized polyisoprene into xylene, mix well, add 4,4-diaminodiphenyl ether, and then raise the temperature to 80-90°C, react for 4-6 hours, cool to room temperature, and then discharge the material to obtain a high temperature resistant added component.

[0016] By adopting the above technical scheme, under the joint action of acetic acid and hydrogen peroxide, the double bonds in the polyisoprene structure are oxidized into epoxy groups to obtain epoxidized polyisoprene, and the epoxy groups in the epoxidized polyisoprene structure undergo a ring-opening reaction with the amino groups in the 4,4-diaminodiphenyl ether structure to obtain a high-temperature resistant additive component with active hydroxyl groups. The high-temperature resistant additive component structure contains a diphenyl ether-based high-temperature resistant rigid ring, which has excellent thermal stability and can improve the high-temperature resistance of polyethylene materials. The polyisoprene molecular chain has good flexibility and elasticity, can absorb and disperse energy when impacted by external forces, reduce the generation and expansion of cracks, and improve the toughness of polyethylene materials. In addition, during the processing process, the active hydroxyl groups in the high-temperature resistant additive component structure can react with the compatibilizer, cross-link with the molecular chains of the polyethylene matrix material, increase the cross-linking density, enhance the cohesion of the polyethylene material, and further improve the toughness and high-temperature resistance of the polyethylene material.

[0017] Furthermore, in S1, the mass fraction of the acetic acid is 85-90%, the mass fraction of the hydrogen peroxide is 32-35%, and the volume ratio of the acetic acid to the hydrogen peroxide is 1:1.

[0018] Furthermore, the compatibilizer is polyethylene grafted maleic anhydride; the lubricant is any one of polyethylene wax, zinc stearate or calcium stearate; and the antioxidant is antioxidant 1010 or antioxidant 1076.

[0019] A method for preparing a PE material containing a nano-reinforcement material comprises the following steps:

[0020] Step 1: Add low-density polyethylene, nano-reinforcement material, high-temperature resistant additive components, compatibilizer, lubricant, and antioxidant into a high-speed mixer, set the speed to 500-800 r / min, and stir for 20-40 minutes to obtain a mixed base material;

[0021] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion, cooling, and granulation to obtain a PE material.

[0022] Furthermore, in step 2, the melt extrusion temperature is 150-200° C., and the screw speed is 150-250 r / min.

[0023] Beneficial effects of the present invention:

[0024] The present invention prepares nano-reinforcement materials and high-temperature resistant additive components, and adds them to polyethylene materials. The prepared PE material has a tensile strength of up to 27.2 MPa, an elongation at break of up to 160.2%, and a Vicat softening temperature of up to 109.2°C. The PE material has excellent mechanical properties, toughness and high-temperature resistance. The PE material can maintain stable performance in a high-temperature environment and is not easily damaged when subjected to external forces, thereby improving safety and reliability, extending the service life of the PE material, and broadening the application field.

[0025] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0027] Figure 1 This is a scanning electron microscope image of the nano C60 and nano reinforced material in the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The preparation methods of the nano-reinforced materials and high temperature resistant additive components used in the following examples and comparative examples of the present invention are as follows:

[0030] 1. Preparation of Nano-Enhancement Materials

[0031] Step A, add 2.5g of nano C60 to a toluene solution, stir evenly, add 1.8g of 3-chloropropylene and 0.02g of azobisisobutyronitrile, introduce nitrogen protection, raise the temperature to 70°C, react for 8h, collect the product, wash, and vacuum dry to obtain modified nano C60;

[0032] Step B: Add 2 g of modified nano C60 into dimethyl sulfoxide, add 2.2 g of terminal hydroxyl hyperbranched polyester and 0.3 g of sodium carbonate, raise the temperature to 80° C., stir and react for 6 h, wash and vacuum dry to obtain a nano-reinforced material.

[0033] The morphology of nano-C60 and nano-reinforced materials was studied and analyzed using a SU8010 scanning electron microscope. Figure 1 It can be seen that the surface of nano-C60 is smooth, while the surface of the nano-reinforcement is rough, which is caused by the successful grafting of hyperbranched polyester onto the surface of nano-C60.

[0034] 2. Preparation of high temperature resistant additive components

[0035] S1. Add 3 g of polyisoprene to a toluene solution, mix well, add 2 mL of 85% acetic acid and 2 mL of 35% hydrogen peroxide, then raise the temperature to 50°C, react for 4 h, precipitate, wash, and vacuum dry to constant weight to obtain epoxidized polyisoprene;

[0036] S2. Add 2.8 g of epoxidized polyisoprene into xylene, mix well, add 1.4 g of 4,4-diaminodiphenyl ether, then raise the temperature to 85°C, react for 5 hours, cool to room temperature, discharge the material, and obtain a high temperature resistant added component.

[0037] The high temperature resistant added component was analyzed for nitrogen by Var io EL Cube element analyzer. The analysis results showed that the nitrogen content in the high temperature resistant added component was 4.62%. The appearance of nitrogen in the high temperature resistant added component was due to the reaction between epoxidized polyisoprene and 4,4-diaminodiphenyl ether, which provided a nitrogen source.

[0038] Example 1

[0039] Preparation of PE materials

[0040] Step 1: Add 65g of low-density polyethylene, 3g of nano-reinforcement material, 4g of high-temperature resistant additive component, 4g of polyethylene grafted maleic anhydride, 0.5g of zinc stearate, and 0.5g of antioxidant 1010 into a high-speed mixer, set the speed to 500r / min, and stir for 20min to obtain a mixed base material;

[0041] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion, the melt extrusion temperature is 150° C., the screw speed is 150 r / min, cool, and granulate to obtain a PE material.

[0042] Example 2

[0043] Preparation of PE materials

[0044] Step 1: Add 75g of low-density polyethylene, 4g of nano-reinforcement material, 5g of high-temperature resistant additive component, 6g of polyethylene grafted maleic anhydride, 1.5g of zinc stearate, and 1.5g of antioxidant 1010 into a high-speed mixer, set the speed to 650r / min, and stir for 30min to obtain a mixed base material;

[0045] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion at a melt extrusion temperature of 175° C. and a screw speed of 200 r / min, cool, and granulate to obtain a PE material.

[0046] Example 3

[0047] Preparation of PE materials

[0048] Step 1: Add 85g of low-density polyethylene, 5g of nano-reinforcement material, 6g of high-temperature resistant additive component, 8g of polyethylene grafted maleic anhydride, 2.5g of zinc stearate, and 2.5g of antioxidant 1010 into a high-speed mixer, set the speed to 800r / min, and stir for 40min to obtain a mixed base material;

[0049] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion, the melt extrusion temperature is 200° C., the screw speed is 250 r / min, cool, and granulate to obtain a PE material.

[0050] Comparative Example 1

[0051] Preparation of PE materials

[0052] Step 1: Add 75g of low-density polyethylene, 4g of nano-reinforcement material, 6g of polyethylene grafted maleic anhydride, 1.5g of zinc stearate, and 1.5g of antioxidant 1010 into a high-speed mixer, set the speed to 650r / min, and stir for 30min to obtain a mixed base material;

[0053] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion at a melt extrusion temperature of 175° C. and a screw speed of 200 r / min, cool, and granulate to obtain a PE material.

[0054] Comparative Example 2

[0055] Preparation of PE materials

[0056] Step 1: Add 75g of low-density polyethylene, 5g of high-temperature resistant additive components, 6g of polyethylene grafted maleic anhydride, 1.5g of zinc stearate, and 1.5g of antioxidant 1010 into a high-speed mixer, set the speed to 650r / min, and stir for 30min to obtain a mixed base material;

[0057] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion at a melt extrusion temperature of 175° C. and a screw speed of 200 r / min, cool, and granulate to obtain a PE material.

[0058] Comparative Example 3

[0059] Preparation of PE materials

[0060] Step 1: Add 75g of low-density polyethylene, 4g of nano C60, 5g of high-temperature resistant additive components, 6g of polyethylene grafted maleic anhydride, 1.5g of zinc stearate, and 1.5g of antioxidant 1010 into a high-speed mixer, set the speed to 650r / min, and stir for 30min to obtain a mixed base material;

[0061] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion at a melt extrusion temperature of 175° C. and a screw speed of 200 r / min, cool, and granulate to obtain a PE material.

[0062] Comparative Example 4

[0063] Preparation of PE materials

[0064] Step 1: Add 75g of low-density polyethylene, 4g of nano-reinforcement material, 5g of polyisoprene, 6g of polyethylene grafted maleic anhydride, 1.5g of zinc stearate, and 1.5g of antioxidant 1010 into a high-speed mixer, set the speed to 650r / min, and stir for 30min to obtain a mixed base material;

[0065] Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion at a melt extrusion temperature of 175° C. and a screw speed of 200 r / min, cool, and granulate to obtain a PE material.

[0066] Performance Testing

[0067] According to the standard GB / T 1040.1-2018, the tensile properties and elongation at break of the samples were tested; according to the standard GB / T1633-2000, the Vicat softening temperature of the samples was tested to determine the high temperature resistance of the samples; the specific test results are shown in the following table:

[0068] Tensile strength / MPa Elongation at break / % Vicat softening temperature / ℃ Example 1 25.4 158.3 108.4 Example 2 27.2 160.2 109.2 Example 3 26.8 159.6 108.7 Comparative Example 1 24.6 118.3 83.6 Comparative Example 2 16.2 154.1 101.5 Comparative Example 3 20.1 157.4 104.6 Comparative Example 4 25.2 153.5 85.4

[0069] It can be seen from the above table that the PE materials prepared in Examples 1 to 3 of the present invention have excellent mechanical properties, toughness and high temperature resistance. Comparative Example 1 does not add high temperature resistant additive components, and cannot utilize polyisoprene grafted diphenyl ether-based high temperature resistant rigid rings, and cannot react with the compatibilizer polyethylene grafted maleic anhydride to generate crosslinks with the matrix molecular chain to further enhance the high temperature resistance and toughness, so the elongation at break and Vicat softening temperature test results are poor; Comparative Example 2 does not add nano-reinforcement material, and cannot utilize nano-C60 to enhance the mechanical properties of the matrix material, and C60 grafted hyperbranched polyester and polyethylene matrix form an interpenetrating network to further improve the mechanical properties of the polyethylene material, so the tensile strength test result is poor; Comparative Example 3 adds nano-C60, which is added directly without modification, has poor compatibility with the polyethylene matrix, may produce agglomeration in the matrix material, resulting in a decrease in the mechanical properties of the material, so the tensile strength test result is poor; Comparative Example 4 adds unmodified polyisoprene, which has limited improvement in the toughness of the matrix material and cannot improve the high temperature resistance of the matrix material, so the elongation at break and Vicat softening temperature test results are poor.

[0070] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A PE material containing nano-reinforcement material, characterized in that: The invention comprises the following raw materials in parts by weight: 65-85 parts of low-density polyethylene, 3-5 parts of nano-reinforcement material, 4-6 parts of high-temperature resistant additive components, 4-8 parts of compatibilizer, 0.5-2.5 parts of lubricant and 0.5-2.5 parts of antioxidant.

2. A PE material containing nano-reinforcement material according to claim 1, characterized in that: The preparation method of the nano-reinforcement material comprises the following steps: Step A, adding nano C60 to a toluene solution, stirring evenly, adding 3-chloropropylene and an initiator, introducing nitrogen protection, raising the temperature to 65-75°C, reacting for 6-8h, collecting the product, washing, and vacuum drying to obtain modified nano C60; Step B, adding modified nano C60 into dimethyl sulfoxide, adding terminal hydroxyl hyperbranched polyester and alkaline catalyst, raising the temperature to 70-90° C., stirring and reacting for 5-8 hours, washing, vacuum drying, and obtaining nano reinforced material.

3. A PE material containing nano-reinforcement material according to claim 2, characterized in that: In step A, the initiator is azobisisobutyronitrile or azobisisoheptanenitrile.

4. The PE material containing nano-reinforcement material according to claim 2, characterized in that: In step B, the alkaline catalyst is potassium carbonate or sodium carbonate.

5. The PE material containing nano-reinforcement material according to claim 1, characterized in that: The preparation method of the high temperature resistant additive component comprises the following steps: S1. Add polyisoprene to a toluene solution, mix well, add acetic acid and hydrogen peroxide, then raise the temperature to 45-55° C., react for 3-5 hours, precipitate, wash, and vacuum dry to constant weight to obtain epoxidized polyisoprene; S2. Add epoxidized polyisoprene into xylene, mix well, add 4,4-diaminodiphenyl ether, and then raise the temperature to 80-90°C, react for 4-6 hours, cool to room temperature, and then discharge the material to obtain a high temperature resistant added component.

6. The PE material containing nano-reinforcement material according to claim 5, characterized in that: In S1, the mass fraction of the acetic acid is 85-90%, the mass fraction of the hydrogen peroxide is 32-35%, and the volume ratio of the acetic acid to the hydrogen peroxide is 1:

1.

7. The PE material containing nano-reinforcement material according to claim 1, characterized in that: The compatibilizer is polyethylene grafted maleic anhydride; the lubricant is any one of polyethylene wax, zinc stearate or calcium stearate; and the antioxidant is antioxidant 1010 or antioxidant 1076.

8. A method for preparing a PE material containing nano-reinforcement material as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add low-density polyethylene, nano-reinforcement material, high-temperature resistant additive components, compatibilizer, lubricant, and antioxidant into a high-speed mixer, set the speed to 500-800 r / min, and stir for 20-40 minutes to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, perform melt extrusion, cooling, and granulation to obtain a PE material.

9. The method for preparing a PE material containing nano-reinforcement material according to claim 8, characterized in that: In step 2, the melt extrusion temperature is 150-200° C., and the screw speed is 150-250 r / min.

Citation Information

Patent Citations

  • A PE nanocomposite material and its preparation method

    CN110229400B

  • Fullerene-containing unsaturated carboxylic acid polymer and preparation method thereof

    CN101265308A

  • C60 fullerene modified abrasion-resistant polyethylene composite material and preparation method thereof

    CN106995545A

  • Modified fullerene synergistic flame-retardant polyene cable material and preparation method thereof

    CN112574495A

  • High-flame-retardant microsphere C60-PMMA composite material and preparation method thereof

    CN113769671A